2022
DOI: 10.1021/acsami.2c13970
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Design from Microstructural Engineering to Binder Optimization Enabling a Practical Carbon Anode with Ultrahigh ICE and Efficient Potassium Storage

Abstract: Potassium-ion batteries (PIBs) are emerging as a powerful alternative to lithium-ion battery systems in large-scale energy storage owing to plentiful resources. Nevertheless, pursuing high-yield anode materials with high initial Coulombic efficiency (ICE) and superior rate capability is still one of the most critical challenges in practical application. Herein, an integrated electrode (PC-x) derived from a petroleum coke precursor (carbon residue rate as high as 89%) is regulated from microstructural engineeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 57 publications
0
8
0
Order By: Relevance
“…An average potassiation potential of 3.3 V vs K/K + was measured for the PBA cathode, and the (S-BP)/G anode delivered an average depotassiation potential of 0.5 V vs K/K + (Figure d), resulting in a total output voltage of 2.85 V in the full cell; this value is higher than reported for other full-cell systems (Figures d, S20, and Table S3). ,,,,, Rate performance test results confirmed delivered discharge capacities of 562, 558, 544, 529, 500, 479, and 462 mA h g –1 at the current densities of 0.26, 0.52, 1.3, 2.6, 5.2, 7.8, and 10.4 A g –1 (Figures d,e, and S21), respectively, where both specific capacities and current densities were calculated based on the mass of the anode. The full cell was then subjected to a long cycle of galvanostatic charge/discharge tests.…”
Section: Results and Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…An average potassiation potential of 3.3 V vs K/K + was measured for the PBA cathode, and the (S-BP)/G anode delivered an average depotassiation potential of 0.5 V vs K/K + (Figure d), resulting in a total output voltage of 2.85 V in the full cell; this value is higher than reported for other full-cell systems (Figures d, S20, and Table S3). ,,,,, Rate performance test results confirmed delivered discharge capacities of 562, 558, 544, 529, 500, 479, and 462 mA h g –1 at the current densities of 0.26, 0.52, 1.3, 2.6, 5.2, 7.8, and 10.4 A g –1 (Figures d,e, and S21), respectively, where both specific capacities and current densities were calculated based on the mass of the anode. The full cell was then subjected to a long cycle of galvanostatic charge/discharge tests.…”
Section: Results and Discussionmentioning
confidence: 59%
“…Results showed that due to the high reversible capacity, suitable working potential, and rate performance of the (S-BP)/G anode, our (S-BP)/G||PBA cell has a very commendable performance combining high energy density and fast-charging performance (212 W h kg –1 at low power, 174 W h kg –1 at power density of 1600 W kg –1 , calculated based on the total mass of the cathode and anode materials), outperforming state-of-the-art PIBs with high-energy high-power densities using other anode materials, e.g., graphite, hard carbon, and organic anodes (Figure g, Table S3). ,,,,, These results are good proof that (S-BP)/G can be used as an optimal anode material for PIBs with high energy and power density.…”
Section: Results and Discussionmentioning
confidence: 64%
“…[12,[105][106][107][108][109] It can be produced from pitch or tar or by pyrolysis of organic polymers such as polyvinyl chloride in a low-oxygen atmosphere. [110][111][112][113] Unlike hard carbon, soft carbon, containing a semi-graphitic structure, has highly ordered graphitic domains arranged in a turbostatic disordered manner. The disordered area in soft carbon is the high-strain region, whereas the graphitic region with higher-order crystallinity is the lowstrain region.…”
Section: Soft Carbonmentioning
confidence: 99%
“…Generally, soft carbon exhibits a sloping potential profile similar to hard carbon but without a low voltage plateau (Figure 4b). [111,120] It has been found that the Li-ion insertion in SCs is highly dependent on the heat-treatment temperature (HTT) during the synthesis. Basically, the low-temperature heattreated SC undergoes three types of Li-ion insertion mechanisms: (a) the adsorption or partial charge transfer of Li-ions on the hexagonal surface or on unstacked carbon layers, which occurs in the potential window of 0.25 to 0.8 V (represented as Type I), (b) intercalation of Li-ions into the carbon layers during charging and discharging in the potential window of 0.0 to 0.25 V (represented as Type II), and (c) the insertion of Li-ion to the microspaces at the carbon cluster edges which occurs at very low potential (represented as Type III) (Figure 4c).…”
Section: Soft Carbonmentioning
confidence: 99%
“…[47,48] Pitch, a representative of soft carbon, is a by-product of the coking or petrochemical industry, which is mainly composed of polycyclic aromatic hydrocarbon molecules. [49][50][51] Owing to the pitch-based carbon materials (PBCMs) with low cost and high carbon yield, which are recognized to be excellent precursors for the preparation of various carbon materials in the field of energy storage, whereas the lack of a relatively comprehensive summary and understanding up to now. In this review, we have systematically investigated the research progress of PBCMs as anode used for alkali metal-ion (Li/Na/K) batteries.…”
Section: Introductionmentioning
confidence: 99%